Evaluating the awareness and implementation level of LCCA in the construction industry of Malaysia - Altaf, M. (Ain Shams University, 2022)
Life cycle cost analysis (LCCA) is an effective indicator to evaluate the economic sustainability of construction projects. LCCA implementation in the Malaysian construction industry remains limited due to its unawareness. This research aims to examine the LCCA awareness and implementation and evaluate the factors that promote LCCA implementation. A survey of 320 Malaysian construction professionals was conducted, followed by statistical data analysis including frequency, mode and relative importance index. According to the findings, 20.1 of newly hired employees in consultancies and contruction firms have minimum education and no awareness, 20â70 had average awareness with some experience in the field and higher degrees, and 4.4 had a high level of awareness with extensive experience in the field. This study provides an in-depth glance into LCCA knowledge, awareness, implementation and factors that can enhance the LCCA implementation in Malaysia and other developing nations. Â© 2022